COMMUNICATIVE ACTIVITIES - Nargiza SALOMOVA (Scholar Express Journal, 2023)
When planning activities focused on speaking skills practice, it might be recommendable to consider which aspect of language we intend our students to work on as for its communicative purpose. We can distinguish between two main views of language: structural and functional. The attention is paid to grammatical system and it deals with ways in which lingustic items can be combined in order to express the intended meaning.
Keywords: Education; specialist; innovative; creativity